HUBUNGAN ANTARA KEPADATAN, TOLERANSI SOSIAL, KEAKRABAN DENGAN RASA SESAK DI PEMUKIMAN PADAT PERKOTAAN - Indra Wahyudi (LPPM Universitas Proklamasi 45, 2006)
Is crowded variable always influenced by density variable, or are there other mediating variables such as social tolerance and familiarization? This research objective is intended to understand the relationship between the density and crowded variables. It is also intended to explain the role of those two mediatingvariables. It is found, that there is no direct relationship between the density and crowded variables (r xI u = .068, p = .0667). However there is negative relationship between the social tolerance and crowded variables (r ^ n = -.323, p = .001). The third hypothesis mentioned that there is negative relationship between the familiarization and crowded variables. Unexpectedly that third hypothesis is significant but having an opposite direction, there is positive correlation between those two variables (r . , = .171, p = .014). Four detailed reasons behind that reversing hypothesis are found at the discussion explanation.",